From the Diary of a Muslim Notary, Damascus 1480-1500: 1500-1480 (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2015)
This article is based on a partially-survived diary, covering the years 1480- 1501, written by Damascene Notary, Shihab ad-Din Ahmad Ibn Tawk (1430- 1509). This diary is an unrivalled primary source for the pre-modern Islamic world, not only due to its sheer scope (about 200 pages in printed edition), but for containing an everyday account on a myriad of issues concerning life in Damascus and its region; and mainly since its author included in the diary long extracts and information from documents which he notarised and that were in his possession, which shed unprecedented light over the society in which he lived. The article focuses on two of the phenomena on which little in known, but much is learnt about from Ibn Tawk’s unique source. The first is the question of divorce, its circumstances, and the accepted financial condition during Ibn Tawk’s days. The second deals with personal rivalries and debates over Sharia law between scholars of the legal schools of thought in Damascus. Ibn Tawk’s accounts on these issues, as on various others his diary deals with, reveal quite a bit about daily lives in a central city in the Islamic world, on the eve of Ottoman occupation, and are a source for ‘everyday history’ or micro-history.